Anti-domestic violence education: Positive legal approach, islamic law and restorative justice magelang - Gunawan; Hamidulloh Ibda; Muhammad Syakur; Sumarjoko; Husna Nashihin (At Turots: Jurnal Pendidikan Islam, 2023)
This study meticulously analyzes the multifaceted issue of Domestic Violence (KDRT) in Magelang Regency, focusing on its root causes, the efficacy of legal resolutions, and the pivotal role of Islamic values. Findings indicate that KDRT is primarily driven by gender role imbalance, economic pressures, and dysfunctional communication, further exacerbated by ingrained patriarchal perceptions. Legal recourse predominantly follows litigation pathways, which are frequently hampered by protracted processes and social stigma, while the restorative justice approach remains sub-optimally and unsystematically implemented. Despite the theoretical relevance of Law No. 23 of 2004 and the principles of Islamic family law, the practical internalization of values such as justice, mutual consultation (musyawarah), and harmonious cohabitation (mu’asyarah bil ma’ruf) within Muslim families in Magelang is notably underdeveloped. This research highlights a significant disparity between the existing legal framework and its practical application. Consequently, the study advocates for multi-structural interventions, including the reinforcement of pre-marital education grounded in Islamic principles, professional family mediation services, and the active engagement of religious leaders. The ultimate objective is to foster a just, peaceful, and transformative approach to KDRT resolution, underpinned by the objectives of Islamic law (maqāshid al-syarī‘ah), thereby cultivating harmonious and violence-free families.